Mempraktekkan Teori dalam Permasalahan Politik dan Lingkungan - Uup Gufron (UIN Sunan Gunung Djati Bandung, 2021)
Conelly and Smith build on a big problem in this book about the difficulty of building and protecting the environment. It is due to many underlying factors. Among them is the human factor who does not have the awareness to protect the environment and nature. This is answered and solved by the author to protect the environment in the next section. At least the author divides the environment into two approaches, namely the political approach and the conventional approach. Politically, the environment must be recognized as a resource on earth that must be protected, because wealth has limitations. Politically too, humans must build a shared awareness by creating a harmonious relationship between humans and nature. This cooperative relationship is framed in ethical understanding between humans and other creatures such as animals, plants, earth, sea, sun, and the like.